Estimation of Monocytes in Patients with Coronary Artery Disease (Medical Forum Monthly, 2024)
Objective: To evaluate the role of monocyte count in patients presenting for coronary artery heart disease and to assess its significance as a risk factor.Design: Cross sectional study.Place and Duration of Study: This study was carried on the patients taken from Coronary Care Unit (CCU) Department of Isra University Hospital, Dewan-e-Mushtaque CCU and from Red Crescent Hospital CCU from May 2011 to October 2011.Materials and Methods: In this study 140 individuals were enrolled to observe the monocyte count in patients with coronary artery disease. In control group 42, Stable Coronary Artery Disease (CAD) 34 and Acute Myocardial Infarction (AMI) 64 individuals were taken. Three ml of blood was collected in EDTA bottles for differential leukocyte count (DLC) from each patient presenting with chest pain in coronary care unit. The total leukocyte count (TLC) and other parameters were determined by different automatic analyzers in the clinical laboratory.Results: In all three groups male predominance with 70%, 64% and 64% in Stable CAD, control, and AMI group was seen respectively. In stable CAD group highest percentage (53%) of patients were seen in 56 to 65 years age followed by 50% of patients of 35-45 years and 42% of patients of 46-55 years in control and AMI group respectively. Both in stable CAD and AMI groups; monocyte count was highly significant in diabetic patients however in individuals with higher BMI; monocyte count was significantly increased in AMI group than stable CAD and control groups.Conclusion: It is concluded from the present study that monocyte count has significant relationship between clinical stages of CAD and diabetic patients. However individuals with higher BMI showed significant high levels of monocyte count in AMI group only.